2004
DOI: 10.2190/ccb6-7m8m-0ca9-6yye
|View full text |Cite
|
Sign up to set email alerts
|

Independent of What? The Independent Medical Examination Business

Abstract: Workers suffering from a work-related health condition frequently are required to undergo examination by a physician chosen by the employer or a Workers' Compensation Insurance Carrier. While the opinions of physicians performing these "Independent Medical Examinations" (IMEs) have been criticized as biased by a conflict of interest, IME advocates assert that the methods used by the IME result in an objective and superior opinion. This article explores this claim to objectivity and superiority. It argues that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Our study showed that the typical result of an IME is a reduction in Workers' Compensation benefits [2]. This analysis was extended in a third paper which surveyed the IME business, concluding that, despite a rhetoric of independence and objectivity, IMEs function as a tool of Workers' Compensation insurance carriers and employers [3]. A fourth study examined trends in Workers' Compensation and disability assessment arguing that an overreliance on methods and information deemed "objective" is eliminating the worker's own history and voice, making it more difficult for occupational disease to be diagnosed and minimizing the extent of disability [4].…”
mentioning
confidence: 54%
“…Our study showed that the typical result of an IME is a reduction in Workers' Compensation benefits [2]. This analysis was extended in a third paper which surveyed the IME business, concluding that, despite a rhetoric of independence and objectivity, IMEs function as a tool of Workers' Compensation insurance carriers and employers [3]. A fourth study examined trends in Workers' Compensation and disability assessment arguing that an overreliance on methods and information deemed "objective" is eliminating the worker's own history and voice, making it more difficult for occupational disease to be diagnosed and minimizing the extent of disability [4].…”
mentioning
confidence: 54%
“…Furthermore, the participants in our study received a copy of their IME report, which is not the case in some systems where workers have to request a copy of the report from the insurer to gain insight [ 27 ]. Some have suggested that an IME does not play a therapeutic role in the recovery process [ 28 ]. Our data do not provide insight into whether the IME report served a therapeutic role; however, this transparency may counteract a possible uncertainty among sick-listed workers.…”
Section: Discussionmentioning
confidence: 99%
“…IMEs have been criticised as harbouring inherent prejudice against the claimant, underdiagnosing and minimising disability 14. We disagree; the fundamental rule of an IME is an honest, complete assessment with verification and support of valid claims of damages or disability 5 15 16.…”
Section: Discussionmentioning
confidence: 99%